Factors associated with dental students' mental health during the COVID-19 pandemic: a longitudinal study - Andréa Neiva da SILVA; Mario Vianna VETTORE (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract The aim of the present study was to examine the relationships between gender, sense of coherence (SOC), social support, perception of academic environment and mental health of dental students during the coronavirus disease 2019 (COVID-19) pandemic. A longitudinal study involving 65 undergraduates enrolled from the first to sixth semesters in the bachelor dental course of Universidade Federal Fluminense, Brazil, was conducted. Baseline data (2018) included age, gender, SOC, social support, stress control and perception of education environment. Depression, anxiety and stress were assessed at baseline (response rate: 93%) and two-year follow-up (2020; response rate: 37%). Structural Equation Modelling was used to test the relationships between independent variables and depression, anxiety and stress during COVID-19 pandemic. Lower social support (β = -0.15), lower stress control (β = -0.20) and lower SOC (β = -0.39) were directly linked to higher depression (β = 0.22). Female gender (β = 0.22), worse perception of educational environment (β = -0.24) and lower SOC (β = -0.57) directly predicted higher anxiety. Female gender (β = 0.18), lower stress control (β = -0.21), and lower SOC (β = -0.46) directly predicted higher stress. The link between gender and both depression and stress, was mediated by stress control. Social support was indirectly linked to depression and stress via SOC. Perception of educational environment mediated the link between SOC and anxiety. Mental health of dental students during COVID-19 pandemic was influenced by demographic characteristics, perception of educational environment, social support and SOC through both direct and indirect pathways.